ANALYSIS OF FACTORS AFFECTING HEPATITIS B IMMUNIZATION COVERAGE IN TODDLERS IN THE WORKING AREA OF THE GAMBIR BARU HEALTH CENTER, ASAHAN REGENCY - Ridwan, Muhammad; Asriwati, Asriwati; Nasution, Ramadhani Syafitri (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
The coverage of Hepatitis B immunization in toddlers in the Gambir Baru Health Center Working Area in 2021 only reached 40.56%, far below the national target. This study aims to analyze the factors that affect the low immunization coverage. The method used is a mix method with an explanatory research design, to be carried out in July-August 2025. The research sample amounted to 66 mothers who had toddlers, obtained through purposive sampling, and 11 informants consisting of key, main, and supporting informants. Quantitative data were analyzed by univariate, bivariate (Chi-square), and multivariate (logistic regression) tests, while qualitative data used interactive analysis. The results showed that the majority of respondents were 36–45 years old (56.1%), had a high school education (53.0%), and worked as self-employed (37.9%). Factors of knowledge, attitude, trust, facilities, husband support, and health worker support affect immunization coverage. Multivariate analysis shows trust is the most dominant factor. Qualitatively, it was found that there is a public belief that the raw materials for Hepatitis B immunization are not halal, so many children are not immunized. It is suggested that the results of this study be a reference and evidence-based for students and health workers related to increasing immunization coverage.